Water Excess and Deficits using Coefficient of Variation of Weekly Rainfall - Mishra, K K (Journal of Agricultural Engineering, 2002)
The weekly rainfall data for a period of 39 years from 1947 to 1985 at Sehore and 35 years weekly rainfall and 17 years evaporation data of Jabalpur, were analysed and the average weekly rainfall (AWR), standard deviation (S) and the coefficient of variation (Cv) were evaluated. The coefficient of variation, in general decreased for the weeks having large amount of rainfall and increased for the weeks receiving scanty rainfall. Relationship between Cv and its probability of occurrence could be expressed by logarithmic equation. Rainfall was dependable on 70 and 84% probable Cv corresponding to 169.29 and 100%, respectively, for Sehore and Jabalpur. The weeks for which Cv was less than 169.29 and 100%, respectively, for Sehore and Jabalpur, the crops would not experience water stress in the area. Thus, a critical value of Cv above or below which the crops would not experience irrigation or drainage in field conditions, could be determined. In general, average weekly rainfall as well as P60 the 60 % probable rainfall, both, varied inversely with Cv. Results of the probability analysis of weekly rainfall were also been utilized in the study. The 23rd and 39th weeks, respectively, represent the onset and end of monsoon. P60 as well as AWR values were more than E, the evaporation as well as ET, the evapotranspiration from 27th to 36th week in Jabalpur and 25th to 38th week in Sehore. The relationship between % cumulative probability of dry days and duration of dry days could be expressed by logarithmic linear model. The Dd of maximum 33 days duration occurred only once in 39 years in 1961 at Sehore. The study could be helpful in deciding crop planting schedules for minimum irrigation requirement and for characterizing the variability of rainfall for different locations.